Initial validation of the Chinese version VIA Youth-96 and age-related changes in character strengths among adolescents - Cheng, Xiaotong; Xu, Shuang; Huang, Yuyan; Qin, Cheng; Liu, Kezhi; Tian, Mingyuan; Liao, Xiaoyuan; Zhou, Xinyi; Xiang, Bo; Chen, Jing; Lei, Wei (Frontiers in Psychology, 2022)
This study aimed to preliminary examine the psychometric properties of the Chinese version 96-item VIA Inventory for Youth (VIA Youth-96) by analyzing the internal consistency, factorial validity, and criterion validity, and to examine the age-related changes in character strengths (CSs) among adolescents. The sample consisted of 959 adolescents aged 10–17 (49.5% boys). Participants completed the Chinese version VIA Youth-96, along with the Perceived Parental Autonomy Support Scale, and questionnaires assessing life satisfaction and self-efficacy online. The Chinese version VIA Youth-96 showed a good fit for the original four-factor structure, and CS scores were significantly correlated with life satisfaction and self-efficacy indicating a good criterion validity of the scale. The internal consistency was 0.54–0.86 for subscales. Moreover, this study revealed significant age-related changes in CSs among adolescents, eight CSs significantly linearly declined by age. These results suggested that the Chinese version VIA Youth-96 is a valid tool for assessing CSs in adolescents and that CSs are declined linearly by age during adolescence.